The strengths and weaknesses of the BIPA curriculum as an Indonesian teaching guideline for foreign speakers: A review of the literature 2018-2023 - Ardiyanti, Warsita Noer (Universitas Negeri Semarang, 2024)
A robust standard in the language teaching process is crucial since this is the primary guidance in the Indonesian language for non-native speakers (BIPA). A systematic literature review of 64 journal articles from 2018 to 2023 reveals comprehensive teaching resources, the flexibility for lecturers to innovate, and incorporating local wisdom in learning materials for students’ cultural immersion, supporting language acquisition. However, weaknesses include overly broad content and insufficient guidance on promoting inclusivity, hindering students' diverse cultural backgrounds. I identified articles matching the selection criteria from titles, aims, methods, to findings. Based on these points, this article highlights more dynamic and adaptive curriculum development needs that respond to global demands. Future studies may focus on developing the curriculum, improving teacher training, and creating inclusive assessments aligned with language proficiency and character development goals to enrich and globalise the BIPA program, supporting the diverse needs of students in an interconnected world.